Promoting Smallholders Carbon Projects in Indonesia - Santoso, Wahyu Yun (Indonesian Journal of International Law, 2011)
As archipelagic country comprising about 17,000 islands and spreading over a total area of 191 million hectares, the prospect of carbon projects in Indonesia are massive. Aside present carbon project activities, the chances to initiate more small scale carbon project are abundant. However, most of the attentions are given for large scale carbon projects as carbon reduction itself still considered as an exclusive interest only. Several lessons can be learn by Indonesian from other developing countries on the implementation of smallholders carbon project. This article aims to briefly describe this issue and purposedly explore the chance of promoting smallholders carbon projects in Indonesia.